Smartphone’s off grid communication network by using Arduino microcontroller and microstrip antenna - Zakaria, Zahriladha; Hussein Al-Hammadi, Yaqdhan Mahmood; Hanoosh, Hatem Oday Hatem; Al-Dhief, Fahad Taha; Saare, Murtaja Ali; Jawad, Mustafa Muhammad; Omran, Alaa Hamza; Abdulbari, Ali Abdulateef (Universitas Ahmad Dahlan (UAD), 2021)
After a major disaster, the present communication system fails in providing the services in the affected area. No means of communication proves to be more dangerous as the rescue and relief operations become more difficult. Our current research is about establishing a network in such a disaster-prone area, which would facilitate to communicate and carry out the rescue missions. This research project used Java to create a fire-chat application and used it with the smartphone android system. It used Bluetooth model HC-05 linked with Arduino UNO by the SPI interface to connect Arduino with the smartphone. The FR-model HCW69 connected with Arduino by using UART to transceiver the message. The microstrip antenna 915 MHz connected with the FR-model HCW69 to give us more distance. The maximum effective range of the transceiver was 1 kilometer, to communicate by forming a mesh network. This application is helpful in the case when the smartphone is out of service; it (smartphone) can be communicated connected to the other nearby users with a message.